The Relationship Between Left and Right PAG in Rat in Unilateral Pain in the Formalin Test - Olya Moshiri; Javad Sajedianfard; Mina Gheisari (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk, 2017)
Abstract Background: Pain is a protective process in the body. There are different pathways for pain control in the central nervous system. Descending pain control system is one of pathways. The periaqueductal gray (PAG) is a structure known for its role in pain transmission and modulation. The aim of this study is to investigate the percent of interaction between the left and right PAG in unilateral left foot induced pain. Materials and Methods: In this study, 60 rats (280+30g) in six groups were used (3test groups and 3 controls groups). In test groups, 0.5 microliter lidocaine was injected in the left PAG, right PAG or both to make local anesthesia. In control groups, 0.5 microliter of normal saline were injected. After 15 minutes, 50 microliter of 2.5% of formalin were injected subcutaneously to right hind paw of rats and nociception was detected in every 15 seconds for one hour. Results: The induction of unilateral pain (left hind paw) in rats, can affect not only the ipsilateral but also the contralateral PAG nucleus. Conclusion: This study showed that the left and right PAG nuclei have significant role on unidirectional nociception in formalin test in rats. The contralateral PAG, however, has a minor effect on nociception.